Reference ranges and cutoff levels of pneumococcal antibody global serum assays (IgG and IgG2) and specific antibodies in healthy children and adults - Rose, M. A.; Buess, J.; Ventur, Y.; Zielen, S.; Herrmann, E.; Schulze, J.; Schubert, R. (Medical microbiology and immunology, 2013)
Pneumococcal antibodies represent the acquisition of natural immunity. Determination of pneumococcal antibodies is an important screening tool for immunodeficiencies. Our study generated reference ranges and cutoff levels for pneumococcal antibody global serum assays correlated to a specific pneumococcal antibody ELISA. Specific pneumococcal antibody levels were measured from 457 children undergoing elective surgery and 46 healthy adult volunteers (88 with previous pneumococcal immunization from both groups), 22 severe immunodeficient subjects with ataxia telangiectasia (A-T, negative controls), and age-matched 36 healthy allergic asthmatics. We determined a representative panel of serotype-specific pneumococcal antibodies (serotype 4, 5, 6B, 7F, 14, 18C, 19F, 23F) by ELISA and global pneumococcal IgG and IgG 2 antibodies by EIA. In vaccine-naïve healthy subjects, initial pneumococcal IgG geometric mean concentrations of 13.1 μg/ml were low in the first year of life and increased over the time, reaching adult levels (70.5 μg/ml) at age 8–12 years. In parallel, IgG 2 antibodies increased from 20.7 % (0.5–1 year old) to adult proportions (>30 %) in preschoolers. Correlation between the pneumococcal IgG screening assay and specific pneumococcal antibody levels was acceptable (Pearson’s coefficient r = 0.4455; p = 0.001). Cutoff levels showed high sensitivity, whereas specificity was high to moderate calculated from correlations with the specific ELISA. We provide reference ranges and cutoff levels for the interpretation of specific antibody determinations in the clinical setting. The global pneumococcal IgG/IgG 2 assay is a suitable screening tool and correlates with the ELISA serotype-specific pneumococcal antibodies. However, results below our cutoff values should be re-evaluated by serotype-specific ELISA testing.